PRELIMINARY STUDY OF APPLICATION OF ROSSMO FORMULA TO IDENTIFY THE MAIN MINERALIZATION ZONE BASED ON THE GEOCHEMICAL DATA WITH CASE STUDY: HIGH-SULPHIDATION EPITERMAL DEPOSIT AT MIWAH, ACEH - Prasetyo, Adi
In criminology, there is one of a geographic profiling equation known as the Rossmo equation which is used to estimate the place of residence of the perpetrator based on some data on the location of the crime scene. The author then got the idea to adopt these equations into the field of geochemical exploration. This research was conducted at the Miwah Gold Project location in the province of Aceh and aims to adopt these equations into the field of geochemical exploration, and is expected to narrow the search area for major mineralization sources based on anomalous geochemical data. The existing equations were slightly modified to suit the characteristics of the distribution of elements. After that, the value of each variable in the equation is determined. After getting all the variables, then a probability map is made based on the variables that have been determined. From these variables, correlations with the geological structure of the study area were also carried out using lineament density. Finally, validation was carried out using the band correlation method between the probability map and the estimated kriging map.